1999
DOI: 10.1345/aph.18198
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Sulfonylureas in a Health Maintenance Organization: A Pharmacy Record–Based Study

Abstract: Our results suggest that factors found to be associated with noncompliant behavior (e.g., being a newly treated patient, self-reported compliance, regimen complexity) can be assessed by physicians and pharmacists as a routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 23 publications
(23 reference statements)
5
75
2
Order By: Relevance
“…Fasting plasma glucose and HbA 1c levels have been noted to drift upwards subsequent to long-term treatment with sulfonylureas, metformin, or diet and exercise (5). Similar results were observed in another claims database analysis, where regimen complexity and low self-reported compliance were also seen for sulfonylurea therapy (7). This lack of glycemic control places diabetic patients at high risk for accelerated disease progression and its sequelae.…”
supporting
confidence: 82%
“…Fasting plasma glucose and HbA 1c levels have been noted to drift upwards subsequent to long-term treatment with sulfonylureas, metformin, or diet and exercise (5). Similar results were observed in another claims database analysis, where regimen complexity and low self-reported compliance were also seen for sulfonylurea therapy (7). This lack of glycemic control places diabetic patients at high risk for accelerated disease progression and its sequelae.…”
supporting
confidence: 82%
“…22,43 Although medication adherence was assessed by an instrument that has not been validated for use in our setting, especially in the format that uses fewer items (e.g., the 4-item instead of 8-item version of the Morisky scale), this instrument has been validated and was found to be reliable and widely used in a variety of medication adherence studies. [49][50][51][52][53] Furthermore, Kripilani et al (2009) used the Morisky Scale as a "gold standard" against which to test a new adherence measurement instrument. 54 Research has indicated that adherence to medication in type 2 diabetes is poor and is considered as one of the main barriers to the benefit of optimal diabetes care and a major cause of unnecessary hospitalization.…”
Section: Randomized Controlled Trial Of Clinical Pharmacy Management mentioning
confidence: 99%
“…It has good reliability and validity. 44,45 This scale asks patients to respond ''yes'' or ''no'' to a set of four questions. A positive response to any question indicates a problem with adherence with a total possible score of 4; higher values indicate poorer adherence.…”
Section: Medication Adherencementioning
confidence: 99%